PENGARUH DISKUSI VERBAL DALAM REVIEW KERTAS KERJA AUDIT TERHADAP KINERJA AUDITOR PADA KANTOR BPK RI PERWAKILAN SULAWESI UTARA - Marunduh, Andrew; Mawikere, Lidya (ACCOUNTABILITY, 2013)
The implementation of accountability in public sector to the establishment of good governance and claen governance in Indonesia was increasing. There are monitoring, control, and inspection as three main aspects to support a good governance. BPK has responsibilities in controlling and giving opinion to the governance financial reports.This study purpose to find out the effect of the verbal discussion in audit working paper review, work experience and motivation to the performance auditors at BPK RI in North Sulawesi.This study chosen BPK RI in North Sulawesi as an object research with population amount was 65 auditors, taken from census method.The independent variables used in this study were verbal discussions  ( X1 )  as well as the dependent variable is the performance auditor  ( Y ) . This study uses simple linear regression analysis and the use of primary data in the form of questionnaires, whereas for hypothesis testing done partially.Based on the analysis results can be known results for the variable Verbal Discussion  ( X1 )   tcount= 5777 and significantly t= 0.000 and 2.000. From these results it can be seen that tcount> tTablecan be stated that HTableorefused and His received and a significant level of 0.000 <0.05 Therefore Verbal Discussion of significant effect on the Performance Auditor.Key Word: BPK RI, performance auditor